Die bydrae van stigma en diskriminasie jeens MIV-positiewe adolessente tot die verspreiding van die MIV- en VIGSpandemie - Beyers, C. (Koers, 2008)
Contribution of stigmatisation and discrimination against HIVpositive adolescents to the occurance of the HIV and AIDS pandemic Although researchers all over the world study ways to curb the HIV and AIDS pandemic, the disease seems to be flourishing in sub-Saharan Africa. Many and varied reasons can be given for the apparently limited success of prevention programmes. This article focuses on stigma and discrimination as contributing factors, and reports on research undertaken to explore perceptions and attitudes towards adolescents who are HIV-positive. The experiences of these adolescents are also described. HIVpositive adolescents were selected in a focused way for individual interviews; parents, teachers and members of the community were selected randomly for focus group interviews. Data analysis revealed that stigma and discrimination are still very much a part of the everyday experiences of HIV-positive adolescents, and that people still harbour the misconception that the infection can be spread through normal interaction, despite information to the contrary. Results were presented after a brief discussion of stigma in general and specifically in the HIV and AIDS context. Characteristics of adolescents that render them especially vulnerable to infection are also presented. In conclusion some suggestions are made with regard to intervention and prevention programmes.